Race Women Internationalists : Activist-Intellectuals and Global Freedom Struggles - Umoren, Imaobong Denis, 1990- (Book collections on Project MUSE., 2018)
"Race Women Internationalists explores how a group of Caribbean and African American women in the early and mid-twentieth century traveled the world to fight colonialism, fascism, sexism, and racism. Based on newspaper articles, speeches, and creative fiction and adopting a comparative perspective, the book brings together the entangled lives of three notable but overlooked women: American Eslanda Robeson, Martinican Paulette Nardal, and Jamaican Una Marson. It explores how, between the 1920s and the 1960s, the trio participated in global freedom struggles by traveling; building networks in feminist, student, black-led, anticolonial, and antifascist organizations; and forging alliances with key leaders. This made them race women internationalists--figures who engaged with a variety of interconnected internationalisms to challenge various forms of inequality facing people of African descent across the diaspora and the continent"--Provided by publisher.